2020
DOI: 10.1177/1948550620931655
|View full text |Cite
|
Sign up to set email alerts
|

Ugliness Judgments Alert us to Cues of Pathogen Presence

Abstract: Little is known about the psychology of ugliness. We propose that ugliness judgments are linked to the behavioral immune system, alerting us to objects that may contain potentially harmful diseases. Exploring this possibility, in five studies ( N = 1,552), we found that ugly human faces (Studies 1a and 1b), ugly animals (Study 2), and—to a lesser degree—ugly buildings (Study 2) elicit disgust controlling for other avoidance-motivated emotional responses. Furthermore, the presence (vs. absence) of dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 48 publications
6
49
0
1
Order By: Relevance
“…Studies 1 and Study 2 found that individuals afford moral standing to beautiful humans and animals through evoked purity intuitions. We also found that people want to protect beautiful humans and animals because of their instrumental value (as well as a negative pathway through sadness in human faces, possibly due to experiencing pity in response to unattractive people; see Klebl et al, 2020). Overall, however, these effects were not explained by mind perception which has been the focus of previous work examining sources of motivation for protecting other people from harm (Gray et al, 2012).…”
Section: Studymentioning
confidence: 59%
See 4 more Smart Citations
“…Studies 1 and Study 2 found that individuals afford moral standing to beautiful humans and animals through evoked purity intuitions. We also found that people want to protect beautiful humans and animals because of their instrumental value (as well as a negative pathway through sadness in human faces, possibly due to experiencing pity in response to unattractive people; see Klebl et al, 2020). Overall, however, these effects were not explained by mind perception which has been the focus of previous work examining sources of motivation for protecting other people from harm (Gray et al, 2012).…”
Section: Studymentioning
confidence: 59%
“…Therefore, beauty perceptions may lead individuals to attribute moral standing to targets because beauty elicits intuitions of moral purity. This is also indirectly supported by research showing that ugly entities elicit disgust (Klebl et al, 2020)-and as such impurity perceptions-as well as evidence suggesting disgust may reduce the moral standing placed on entities (Oaten et al, 2011). For example, people avoid individuals with facial disfigurement, and this has been found to be mediated by disgust (Park et al, 2013;Ryan et al, 2012).…”
Section: Beauty Moral Standing and Puritymentioning
confidence: 72%
See 3 more Smart Citations